2011
DOI: 10.1158/0008-5472.can-10-3192
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased Lymphangiogenesis and Lymph Node Metastasis by mTOR Inhibition in Head and Neck Cancer

Abstract: Despite our improved understanding of cancer, the 5-year survival rate for head and neck squamous cell carcinomas (HNSCC) patients remains relatively unchanged at 50% for the past three decades. HNSCC often metastasize to locoregional lymph nodes, and lymph node involvement represents one of the most important prognostic factors of poor clinical outcome. Among the multiple dysregulated molecular mechanism in HNSCC, emerging basic, preclinical, and clinical findings support the importance of the mTOR signaling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 41 publications
8
125
0
3
Order By: Relevance
“…Cancer cells induce the formation of new lymphatic vessels, which are characterized by discontinuous cell-cell junctions and a lack of pericytes or vascular smooth muscle cells, via secretion of lymphangiogenic growth factors with promotion of tumor cell dissemination to LNs (29,42). Importantly, diminishing lymphangiogenesis in vivo prevents regional LN metastasis and prolongs animal survival times in studies of other cancer types (43,44). Herein, our results show that downregulation of BLACAT2 plays dual antilymphatic metastasis roles, including prevention of lymphangiogenesis and inhibition of cell invasiveness, suggesting that BLA-CAT2 may serve as a potential target for intervention in bladder cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Cancer cells induce the formation of new lymphatic vessels, which are characterized by discontinuous cell-cell junctions and a lack of pericytes or vascular smooth muscle cells, via secretion of lymphangiogenic growth factors with promotion of tumor cell dissemination to LNs (29,42). Importantly, diminishing lymphangiogenesis in vivo prevents regional LN metastasis and prolongs animal survival times in studies of other cancer types (43,44). Herein, our results show that downregulation of BLACAT2 plays dual antilymphatic metastasis roles, including prevention of lymphangiogenesis and inhibition of cell invasiveness, suggesting that BLA-CAT2 may serve as a potential target for intervention in bladder cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Indirectly, tumor-induced lymphangiogenesis is correlated with metastasis in a number of cancer models, including colorectal, breast, prostate, head and neck cancer, and melanoma [93][94][95][96][97][98][99], and expression of Semaphorin…”
Section: Lymphangiogenesis and Cancermentioning
confidence: 99%
“…The precise molecular events that signal for lymphangiogenesis are poorly understood. Inhibition of the mTOR pathway decreases lymphangiogenesis and metastasis, and prolongs survival in a head and neck cancer animal model [99].…”
Section: Lymphangiogenesis and Cancermentioning
confidence: 99%
“…Although there is evidence suggesting that activation of the mTOR pathway stimulates lymphangiogenesis (Kobayashi et al 2007;Patel et al 2011;Luo et al 2012) and hence may underlie LAM cell lymphatic differentiation, a recent study by our group stands against such a possibility (Badri et al 2013). In that study, we examined the TSC1 and TSC2 genes by ultra-deep sequencing in 10 of the 19 late-stage LAM cases included here and found that 2 of those cases had neither TSC2 nor TSC1 mutations identified and no activation of the mTOR signaling cascade.…”
Section: Discussionmentioning
confidence: 90%